(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Recently Brenner [Physica A 349, 60 (2005)] proposed a modified Navier-Stokes set of equations. Based on some theoretical arguments and some limited experiments, the model is expected to be able to describe flows with a finite Knudsen number. In this work, we apply this model to the plane Poiseuille flow driven by a force, and compare the results with the Direct Simulation Monte Carlo (DSMC) measurements. It is found that Brenner's model is inadequate for flows with a finite Knudsen number.